2020
DOI: 10.1002/prep.201900392
|View full text |Cite
|
Sign up to set email alerts
|

ADN Recrystallization and Microencapsulation with HTPB by Simple Coacervation

Abstract: Ammonium dinitramide (ADN) has been considered the potential substitute for ammonium perchlorate in solid green propellants. However, it has also some drawbacks due to its high hygroscopicity and chemical incompatibility with some of the components present in composite propellant formulations. On the other hand, ADN melts at temperatures below degradation, which makes emulsion crystallization an important method to prepare spherical ADN particles that benefit both propellant slurry processing and casting. Sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The microencapsulated ADN were subjected to the dissolution test that consists of immersing the particles straight into distilled water; water passes through the structural defects in the capsule and starts dissolving the ADN inside, until it is completely dissolved, leaving the empty capsule floating on the water surface. For details, please refer to our previous work [12]. The dissolution time and rate are the parameters associated with capsule permeability; the first is the span between the moment of the immersion of the particle and the floating, and the second is the ratio of ADN particle mass to dissolution time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The microencapsulated ADN were subjected to the dissolution test that consists of immersing the particles straight into distilled water; water passes through the structural defects in the capsule and starts dissolving the ADN inside, until it is completely dissolved, leaving the empty capsule floating on the water surface. For details, please refer to our previous work [12]. The dissolution time and rate are the parameters associated with capsule permeability; the first is the span between the moment of the immersion of the particle and the floating, and the second is the ratio of ADN particle mass to dissolution time.…”
Section: Methodsmentioning
confidence: 99%
“…A Büchi chiller, model F‐114, was employed as the cooling circulator, whose temperature remained below 10 °C; after solidifying, the round ADN particles were filtered, washed with dichloromethane, and remained inside a desiccator to remain dry; obtaining round ADN particles with radius under 600 μm. The process parameters applied in this method were given in a previous work [12]. The apparatus is schematically depicted in Figure 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silva et al used polyurethane made from end-hydroxy polybutadiene as a coating material to encapsulate spherical ADN by microencapsulation. The results demonstrated the good compatibility between this polyurethane coating material and ADN, which led to good coating performance [88]. Santosh et al coated ADN particles with ethyl cellulose or polymethylmethacrylate (PMMA).…”
Section: Mechanism Advantages Disadvantagesmentioning
confidence: 95%
“…The hygroscopicity was 10%, which still could not meet the requirements of propellant loading. Oliveira Silva et al 23 used polyurethane made of hydroxyl-terminated polybutadiene as a coating material, and moisture absorption tests showed that there was an important relationship between the formation of capsules and the number of layers as well as the processing time. The chemical compatibility between the capsules and ADN was determined at 60 ○ C, making it possible to use them as a protective coating.…”
Section: Introductionmentioning
confidence: 99%